2014
DOI: 10.1155/2014/403472
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinyl alcohol): Physical Approaches to Designing Biomaterials for Biomedical Applications

Abstract: Poly(vinyl alcohol) is a non-toxic, biosynthetic polymer and biocompatible polymer that has the ability to form hydrogels either via chemical or physical crosslinking. Whilst chemical crosslinking provides greater control on the properties of the resultant hydrogel, physically crosslinked hydrogels or blends with other biocompatible polymers are more suited for biomedical applications. In this paper we report a systematic study on the effect of varying concentrations of PVA, physical methods of crosslinking, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 21 publications
3
32
0
1
Order By: Relevance
“…Gupta et al [43] found close values (40–42.5 °C) for PVA materials prepared by freeze-thawing with 8–14% of the polymer. Higher values (70.5–73.4 °C) were observed by Nkhwa et al [44] for FT gels obtained from solutions with 10%–30% PVA. For CD hydrogels prepared with the same PVA concentrations (10%–30%), they verified that T g decreased from 73.4 to 58 °C when the polymer concentration increased.…”
Section: Resultsmentioning
confidence: 66%
“…Gupta et al [43] found close values (40–42.5 °C) for PVA materials prepared by freeze-thawing with 8–14% of the polymer. Higher values (70.5–73.4 °C) were observed by Nkhwa et al [44] for FT gels obtained from solutions with 10%–30% PVA. For CD hydrogels prepared with the same PVA concentrations (10%–30%), they verified that T g decreased from 73.4 to 58 °C when the polymer concentration increased.…”
Section: Resultsmentioning
confidence: 66%
“…The networks were further subjected to one cycle of freeze thawing with the formulations shown in Table 1. Cryogelation was selected to physically cross link PVA since it is an attractive method of production of micro or macro porous materials [12] without use of crosslinking agents, initiators, activators or solvents that in addition allows control on textural, structural and absorption characteristics. Furthermore, it enables to vary the extent of crosslinks by altering factors such as the concentration of the macromolecules in solution and number of freeze-thawing cycles, which also allows a handle on altering the physical properties as per requirements.…”
Section: Resultsmentioning
confidence: 99%
“…Aqueous solutions of PVA were prepared at concentrations of 10% (PVA10) and 20% (PVA20) by heating the granules at 121 °C until fully dissolved. Solutions were allowed to cool down and poured into moulds before subjecting to various cycles of freeze drying (1, 2 and 3) for 24 h and thawing, to obtain PVA10-1FT, PVA10-2FT and PVA10-3FT and PVA20-2FT [12].…”
Section: Methodsmentioning
confidence: 99%
“…C-O stretching vibration combined with OH bending vibration shows a high-intensity peak at 1083 cm À1 . 29 The sharp peak at 840 cm À1 existing in the FTIR spectrum is ascribed to the between ZB Nps and polymeric PVA. All these results con¯rm the fact that PVA forms a compositē lm with the added FR additives.…”
Section: Ftir Analysismentioning
confidence: 99%